Dyspnea and the Varying Pathophysiologic Manifestations of Chronic Obstructive Pulmonary Disease Evaluated by Cardiopulmonary Exercise Testing With Arterial Blood Analysis - Kagawa, Hiroyuki; Miki, Keisuke; Kitada, Seigo; Miki, Mari; Yoshimura, Kenji; Oshitani, Yohei; Nishida, Kohei; Sawa, Nobuhiko; Tsujino, Kazuyuki; Maekura, Ryoji (Frontiers in Physiology, 2018)
Background: Patients with chronic obstructive pulmonary disease (COPD) show varying mechanisms of exertional dyspnea with different exercise capacities. Methods: To investigate the pathophysiologic conditions related to exertional dyspnea, 294 COPD patients were evaluated using cardiopulmonary exercise testing (CPET) with arterial blood analyses, with the patients classified into two groups according to their exercise limitation: the leg fatigue group (n = 58) and the dyspnea group (n = 215). The dyspnea group was further subdivided into four groups based on peak oxygen uptake (VO2 in mL/min/kg): group A (<11), group B (11 to <15), group C (15 to <21), and group D (≥21). Results: In the dyspnea group, group A (n = 28) showed the following findings: (i) the forced expiratory volume in one second was not correlated with the peak VO2 (p = 0.288), (ii) the arterial oxygen tension (PaO2) slope (peak minus resting PaO2/VO2) was the steepest (p < 0.0001) among all subgroups, (iii) reduced tidal volume (VT) was negatively correlated with respiratory frequency at peak exercise (p < 0.0001), and (iv) a break point in exertional VT curve was determined in 17 (61%) patients in group A. In these patients, there was a significant negative correlation between bicarbonate ion (HCO3-) levels at peak exercise and VT level when the VT-break point occurred (p = 0.032). In group D (n = 46), HCO3- levels were negatively correlated with plasma lactate levels (p < 0.0001). In all subgroups, the HCO3- level was negatively correlated with minute ventilation. The dyspnea subgroups showed no significant differences in the overall mean pH [7.363 (SD 0.039)] and Borg scale scores [7.4 (SD, 2.3)] at peak exercise. Conclusions: During exercise, ventilation is stimulated to avoid arterial blood acidosis and hypoxemia, but ventilatory stimulation is restricted in the setting of reduced respiratory system ability. These conditions provoke the exertional dyspnea in COPD. Although symptom levels were similar, the exertional pathophysiologic conditions differed according to residual exercise performance; moreover, COPD patients showed great inter-individual variability. An adequate understanding of individual pathophysiologic conditions using CPET is essential for proper management of COPD patients.